2013
DOI: 10.1111/jmwh.12043
|View full text |Cite
|
Sign up to set email alerts
|

Exit Interviews from Adolescent Girls Who Participated in a Sexual Risk‐Reduction Intervention: Implications for Community‐Based Health Education Promotion for Adolescents

Abstract: Introduction The purpose of this study was to invite girls who participated in a gender-specific, sexual risk-reduction intervention to describe their experiences and identify program characteristics most or least beneficial to their involvement. Method Semi-structured interviews were completed with 26 African American, low income girls ages 15–19 who had participated in a sexual risk reduction intervention as part of a randomized controlled trial. The girls were interviewed after completing a 12-month post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 15 publications
1
55
0
Order By: Relevance
“…Historically, risk reduction programs for sexually experienced youth have focused on return to abstinence, use of condoms or contraceptive devices or reduced frequency of intercourse [ 30 ]. Our findings support the need to include skill-based messages on strategies for reducing risk such as the use of assertive statements and introduction of sex only with trusted partners [ 45 ].…”
Section: Discussionsupporting
confidence: 75%
“…Historically, risk reduction programs for sexually experienced youth have focused on return to abstinence, use of condoms or contraceptive devices or reduced frequency of intercourse [ 30 ]. Our findings support the need to include skill-based messages on strategies for reducing risk such as the use of assertive statements and introduction of sex only with trusted partners [ 45 ].…”
Section: Discussionsupporting
confidence: 75%
“…Participants reported on history of pregnancy, childbearing, and parenting. Participants also reported their current and past risk behaviors including number of sexual partners and the number of sexual episodes of protected (condoms) and unprotected (without condoms) vaginal and anal sex (Morrison-Beedy, 2012; Morrison-Beedy, Carey, Crean, & Jones, 2011; Morrison-Beedy, Jones et al, 2013; Morrison-Beedy, Passmore, & Carey, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, four questions, previously documented for reliability and validity, assessed alcohol use in study participants (Carey et al, 2000; Carey et al, 2004; Carey et al, 1997; Morrison-Beedy et al, 2011). The questions assessed: (a) any alcohol use in the past 3 months, (b) quantity of alcohol, (c) frequency of use, and (d) binge-drinking (4 or more drinks on any one occasion; Morrison-Beedy et al, 2011; Morrison-Beedy et al, 2006; Morrison-Beedy, Passmore, & Carey, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…For intervention trials, like COSTOP, that include provider–client interactions, exit interviews with clients are recommended to monitor their understanding of the advice that was provided [3] . Laboratory based tests to detect the treatment under study are often non-existent or expensive, and therefore exit interviews conducted by independent research staff are an important way in which to evaluate adherence to study product [4] Findings from exit interviews have been reported in brief in many accounts of trial findings but the experience of using this technique has only occasionally been presented in standalone papers [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%